String Processing and Information Retrieval : 22nd International Symposium, SPIRE 2015, London, UK, September 1-4, 2015, Proceedings - Iliopoulos, Costas; Puglisi, Simon; Yilmaz, Emine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 22nd International Symposium on String Processing and Information Retrieval, SPIRE 2015, held in London, UK, in September 2015. The 28 full and 6 short papers included in this volume were carefully reviewed and selected from 90 submissions. The papers cover research in all aspects of string processing, information retrieval, computational biology, pattern matching, semi-structured data, and related applications.
Keywords: Information storage and retrieva; Optical pattern recognition; Computer software; Data mining; Database management; Information Storage and Retrieval; Pattern Recognition; Algorithm Analysis and Problem Complexity; Data Mining and Knowledge Discovery; Database Management